2004
DOI: 10.1038/sj.ejcn.1601977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breast milk of diabetic mothers on bodyweight of the offspring in the first year of life

Abstract: Objective: There is increasing evidence that in healthy populations, breast-fed infants are leaner than formula-fed infants. It is of interest to know the effects of breast-feeding on infant weight in case of maternal diabetes, given the high incidence of fetal macrosomia and risk of childhood obesity in this population. Design and Subjects: As part of a nation-wide study in the Netherlands on diabetes and pregnancy, 229 women with Type 1 diabetes were sent a questionnaire on weight and height of their infant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…Effects of milk consumed in this 1st week were confirmed in the same cohort, after accounting for intake in the 2nd to 4th week of life (13). However, among offspring of mothers with type 1 diabetes, Kerssen et al (15) found no association of infant feeding modality in the first 6 weeks of life with weight or BMI at 1 year of age. Pettitt et al (14) found that among Pima Indians, a protective effect of breastfeeding on subsequent development of type 2 diabetes in offspring appeared to be present in mothers with or without diabetes during pregnancy, although the sample size was small.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Effects of milk consumed in this 1st week were confirmed in the same cohort, after accounting for intake in the 2nd to 4th week of life (13). However, among offspring of mothers with type 1 diabetes, Kerssen et al (15) found no association of infant feeding modality in the first 6 weeks of life with weight or BMI at 1 year of age. Pettitt et al (14) found that among Pima Indians, a protective effect of breastfeeding on subsequent development of type 2 diabetes in offspring appeared to be present in mothers with or without diabetes during pregnancy, although the sample size was small.…”
mentioning
confidence: 80%
“…However, several issues are unresolved, including the potential for residual confounding to explain the effect (10,11). Moreover, it is possible that the impact of breast-feeding on childhood obesity may be attenuated or reversed among children whose mothers have diabetes (12)(13)(14)(15) or may be enhanced if mothers are overweight or obese (16,17).…”
mentioning
confidence: 99%
“…In populationbased studies, breast-feeding has been suggested to be protective against obesity and diabetes in later life (5,7,8). Whether this is the case in a population of diabetic women has been questioned (24,25). Breast milk of diabetic mothers is characterized by increased glucose and insulin concentrations, as seen particularly in the analysis of colostrum samples (24).…”
Section: Breast-feeding In Women With Diabetesmentioning
confidence: 99%
“…A number of subsequent studies addressed this question and came to heterogeneous results. While two studies pointed towards unfavourable consequences of breastfeeding for risk of overweight and impaired glucose tolerance in ODM [4,19] , some recent studies showed benefi cial effects of a prolonged breastfeeding, i.e., longer than 4 months, in this special risk group [5,18,21] . For the interpretation of these different results, it is important to realize that a number of confounders must be considered, including e.g., time point of exposure, type of maternal diabetes, age at follow-up and maternal body weight [29] .…”
Section: Discussionmentioning
confidence: 99%